Noções de passado, presente e futuro entre crianças indígenas (Javaé) e crianças não indígenas (Colégio Claretiano Coração de Maria) - Silva, Luciana Leite da (2014)
The proposal of analyzing the historical ideas of children from different cultural contexts has the aim of evaluating the reaching of theoretical references, that conducts the field of Didactics of History in Brazil and the intercultural approaches in the education of History. This research comes from a paradox lived in the classroom. In one side, the politics of ethnic and races. On the other side, the presence of Eurocentric tales in books as much as in teachers' and students' conversation. The experience in the course of Intercultural Education for Indian Teachers opened new perspectives of analyses about this question, as showed other problems that mark the conflituous relations between the indian and non-indian societies. Beyond the land questions, as are frequently showed in the media, we aim to ascertain the different ways of narrating the being in the world, so that we can think about an intercultural historical learning that treats the diversity in a more embracing way than the antiracists speeches.